2017
DOI: 10.1093/jscr/rjx014
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery dissection following a posterior cervical foraminotomy

Abstract: Vertebral artery dissection following a posterior cervical foraminotomy with rhizolysis of the subaxial spine has not been described before. A 46-year-old lady underwent the procedure for a left C6 radiculopathy with a focal disc herniation with no intraoperative complications. Seven hours post-operatively, she developed a right homonymous hemianopia, thalamic dysphasia, gait and memory impairment. Imaging demonstrated an occlusion to the left vertebral artery from C7/T1 to C4 with a dissection flap noted at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Consequently, most clinical and anatomical studies have focused on avoiding vertebral artery injury in upper cervical surgery. However, vertebral artery injury can also occur during posterior cervical foraminotomy in the subaxial spine [3,11]. The incidence of vertebral artery injury is predicted to increase because a growing number of surgeons are performing endoscopic cervical foraminotomies [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, most clinical and anatomical studies have focused on avoiding vertebral artery injury in upper cervical surgery. However, vertebral artery injury can also occur during posterior cervical foraminotomy in the subaxial spine [3,11]. The incidence of vertebral artery injury is predicted to increase because a growing number of surgeons are performing endoscopic cervical foraminotomies [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al reported a case of spinal dural injury caused by the intraoperative drilling process, 24 and Stephen et al reported a case of vertebral artery injury during posterior cervical surgery. 25 Based on the above complications, Nkamura S et al designed an internal retractor to avoid nerve damage, but it was di cult to popularize. 26 The technique of anchoring the projection point on the inner upper edge of the pedicle that was used in this study was performed under direct endoscopic vision.…”
Section: Discussionmentioning
confidence: 99%